Population Ahead. - Francis, Roy G. (University of Minnesota Press, 1958)
The Population Ahead was first published in 1958. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. This volume brings together the thinking and viewpoints of specialists from various pertinent fields for a discussion of factors bearing on the quality of future populations of the world. The discussions center around three fundamental questions: Is the human population growing at a rate which threatens the standards of living to which most of tits individuals aspire? Is the genetic composition of the population tending in directions which are harmful to the common good? What can and should be done, if the answer to either of the foregoing questions is yes?The chapters, by nine different contributors, are based on the papers given at a conference on population problems held at the University of Minnesota in 1957. In addition, discussion and comments by six other participants in the conference are included.